2017
DOI: 10.1530/eje-16-0725
|View full text |Cite
|
Sign up to set email alerts
|

Can we predict relapse in Graves’ disease? Results from a systematic review and meta-analysis

Abstract: This analysis found several risk factors to predict relapse in Graves' disease, which can be combined in a risk score. Prospective studies should evaluate the prognostic accuracy of such a score to guide treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(90 citation statements)
references
References 59 publications
5
79
0
6
Order By: Relevance
“…The article presents new information regarding patterns of disappearance of serum TRAb concentrations over time, which appear to have an impact on the probability of remission. Unlike other studies, which found useful predictors of remission in baseline clinical and laboratory tests (e.g.,7,8), the authors of this report found no baseline parameter predicting the likelihood of remission.…”
mentioning
confidence: 54%
“…The article presents new information regarding patterns of disappearance of serum TRAb concentrations over time, which appear to have an impact on the probability of remission. Unlike other studies, which found useful predictors of remission in baseline clinical and laboratory tests (e.g.,7,8), the authors of this report found no baseline parameter predicting the likelihood of remission.…”
mentioning
confidence: 54%
“…Another meta-analysis evaluating 54 trials and 7,595 participants showed several risk factors predicting persistence (49%) in GD [74]. Orbitopathy, smoking, thyroid volume, free T4, total T3, and TSH-R-Ab were significantly associated with relapse.…”
Section: Relapse After a Course Of Atd Treatmentmentioning
confidence: 99%
“…TSI levels and the age or sex did not show significant associations with recurrence. 7) In another studies showed average age at diagnosis was significantly younger at non-remission group compared with remission group after antithyroid drug therapy for GD. 8,9) But, our data showed opposite result.…”
Section: Resultsmentioning
confidence: 93%